Using coherence factor to improve the quality of reflector images in ultrasonic testing - Bazulin, E. G. (Russian journal of nondestructive testing, 2017)
When running ultrasonic testing, it is possible to analyze reflector images that have been restored by the method of digital focusing with an antenna (DFA). To improve the quality of the reflector images, one can use a coherence factor (CF) or a sign coherence factor (SCF) obtained from the calculated delay times instead of counting echo signals. The images obtained with the calculation of the coherence factor make it possible to increase the signal-to-noise ratio and front resolution. It has been demonstrated by numerical and model experiments that reconstructing the CF- and SCF-images of reflectors is efficient when registering echo signals by both ordinary and thinned (TAA) antenna arrays, in which the distance between neighboring elements is much greater than the wavelength.